Spectral Insights into Epidemic Dynamics on Complex Networks - Dr. NareshKumar. S,; Ms. .Sushama.C, (Utilitas Mathematica, 2025)
The Laplacian spectrum of a graph refers to the spectrum of its Laplacian matrix, which is a matrix derived from the graph's adjacency matrix. This spectrum carries important information about the graph's structure and properties. Here are several key applications of the Laplacian spectrum in graph theory and related fields. The spread of diseases through social or biological networks can be studied using the Laplacian spectrum. Eigenvalues and eigenvectors of the Laplacian matrix help in understanding the dynamics of disease transmission and designing effective intervention strategies. The eigenvalues and eigenvectors of the Laplacian matrix can help identify key nodes (individuals or locations) within a social or biological network that play crucial roles in disease transmission. High eigenvector centrality indicates nodes that are influential in spreading the disease and are therefore important targets for intervention strategies such as vaccination or quarantine. The Laplacian spectrum provides insights into the resilience of the network to disease outbreaks. Networks with higher algebraic connectivity (higher values of the second smallest eigenvalue) are more tightly connected, potentially leading to faster disease spread. Understanding these properties helps in assessing the risk of widespread outbreaks and planning mitigation measures.